Dapora Forest - a gond Temple - Yellurkar, D. D. (Indian Forester, 1976)
Dapora 'C' class forest, falling in Wani Range of Yeotmal Division, is zealously protected by local tribals (Gouds) who consider this forest as a temple an abode of their deity 'Phersopen'. This typical instance of the protection of a forest from human interference out of religious belief is graphically described.